Gamma-radiation of Glossina palpalis gambiensis revisited: effect on fertility and mating competitiveness - (:unkn) unknown (My University, 2023)
African animal trypanosomoses are vector-borne diseases that cause enormous livestock losses in sub-Saharan Africa, with drastic socio-economic impacts. Vector control in the context of an area-wide integrated pest management program with a sterile insect technique component requires the production of high-quality sterile male tsetse flies. In our study, we evaluated the effect of irradiation on the fecundity of Glossina palpalis gambiensis to identify the optimal dose that will induce maximum sterility while maintaining biological performance as much as possible. In addition, male mating performance was evaluated in semi-field cages. The irradiation doses used were 90, 100, 110, 120, 130, 140, and 150 Gy, and untreated males were used as the control. The results showed that pupal production and emergence rates were higher in batches of females that had mated with fertile males than in those that had mated with irradiated males with any experimental dose. A dose of 120 Gy administered to male flies induced 97–99% sterility after mating with virgin females. For the semi-field cage experiments, males irradiated with 120 Gy showed good sexual competitiveness as compared to fertile males and those irradiated with 140 Gy, considering the level of filling of spermatheca and the number of pairs formed. The optimal radiation dose of 120 Gy found in this study is slightly different from the traditional dose of 110 Gy that has been used in several eradication programmes in the past. The potential reasons for this difference are discussed, and an argument is made for the inclusion of reliable dosimetry systems in these types of studies.
Keywords: African Research